Growth performance of Magnolia champaca (L.) Baill. ex Pierre using different types of mulching at Montane Rainforest in Cameron Highlands, Pahang, Malaysia - Rahmani, Wahidullah (2021)
Tropical Montane Cloud Forest (TMCF) is one of the ecosystems most threatened by deforestation, fragmentation and global climate change. The study conducted on Sg. Terla A at Forest reserved Cameron Highlands with mean elevation 1478m above sea level. The objectives of this study are; (i) to determine the growth performance and biomass of Magnolia champaca planted under different types of mulching at the degraded area, and (ii) to determine the effect of different types of mulching on soil properties at degraded area. In this study Randomized Complete Block Design (RCBD) was used. The data on growth performance were taken since July 2019 until July 2020. The plant was measured for above and below biomass. The soil samples were taken to study the effect of different mulching materials on the soil characteristic. The results in this study showed that mulching had no significant effect on plant height, diameter breast height, and root collar diameter, and chlorophyll content between treatments. Although oil palm mulching treatment had a greater effect on plant height, root collar diameter and diameter breast height growth among treatments. Mulching showed a significant effect on root diameter and main root length among treatments. Root direction towards to sun direction among plants was varied. The root horizontal and vertical were significant difference between treatments while coconut treatment showed the highest value and oil palm showed the lowest among treatments. Mulching had no significant effect on root shoot ratio among treatments. Compared between treatments, oil palm treatment was significantly higher than other treatments. Furthermore, 75% of plants had coiling while 25% had no coiling. Dry biomass fraction was not showed significant differences between stem, branch, leaf and root in coconut, oil palm, plastic and control treatments. The highest value of roots, leaves and branches were found in coconut treatment while the lowest was found in control treatment. The highest amount of stem was found in coconut and the lowest was found in oil palm treatment. There was no significant difference for dry above and below biomass between treatments. The highest amount of above and below biomass was found in coconut while the lowest value was found in oil palm among treatments. Moreover, soil compaction showed a significant difference between treatments. The maximum value showed in the control treatment while the minimum value was found in the coconut mulching treatment. Furthermore, the soil texture was clay 20%, silt 60 %, and 20 % sand for all treatments. Mulching had a significant effect on soil pH. The minimum pH value (4.28 pH) was recorded in plastic mulching, and the maximum value (4.57 pH) was found in coconut mulching treatment. Mulching had a highly significant effect on soil moisture content. The maximum value (17.92 %) was recoded in plastic while the minimum was showed in oil palm mulching (16.12 %) treatment. Mulching did not show a significant effect on soil organic carbon, soil organic matter, soil total nitrogen, and soil available phosphorus and topsoil and subsoil between treatments. However, mulching showed a strongly significant effect on exchange potassium and soil sulfur among treatments while topsoil and subsoil did not show a significant effect between treatments. In conclusion, the results indicate that different types of mulching have no significant effect on tree growth rate although it improves the growth rate, root development, biomass, and soil properties on the degraded areas.